2017
DOI: 10.1111/iju.13442
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation on the effect of interobserver variability of digital rectal examination on the performance of the Rotterdam Prostate Cancer Risk Calculator

Abstract: Slight differences in digital rectal examination findings seem to have very limited impact on the performance of the Rotterdam Prostate Cancer Risk Calculator. Therefore, this can be considered a useful prostate biopsy outcome prediction tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…The summary data for these studies are presented in Table 2, in chronological order. 5,12,13,[24][25][26][27][28][29] Several studies have indicated that that there was a tendency for DRE to over or underestimate the reference PGV, such that the estimation of the PGV by DRE was most accurate when the PGV was close to the median value of the reference PGV for the patients in those studies. DRE tended to overestimate the PGV when the PGV was smaller than the median reference value and tended to underestimate the PGV when it was larger.…”
Section: Resultsmentioning
confidence: 99%
“…The summary data for these studies are presented in Table 2, in chronological order. 5,12,13,[24][25][26][27][28][29] Several studies have indicated that that there was a tendency for DRE to over or underestimate the reference PGV, such that the estimation of the PGV by DRE was most accurate when the PGV was close to the median value of the reference PGV for the patients in those studies. DRE tended to overestimate the PGV when the PGV was smaller than the median reference value and tended to underestimate the PGV when it was larger.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, no literature concerning the interrater agreement of DRE has been published. Interrater agreement has only been studied in vaginal digital assessment concerning the pelvic floor function and digital rectal examination in the context of prostate cancer [31][32][33]. Overall, the agreement was substantial to almost perfect.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the probability of missing both PCa and csPCa after new mpMRI revealed no high-grade PIRADS lesions appears to be minimal. In the RPCRC, the DRE-result plays a relatively important role in the decision-making [25]. Some men might have been erroneously labelled inconspicuous while having a pathologic DRE (e.g., cT2a), resulting in low-risk stratification.…”
Section: Discussionmentioning
confidence: 99%